Perancangan Sistem Informasi Pencatatan Kas Menggunakan Framework Laravel - Eka Safitri; Dania Febyola Hanum; Resmi Ranti Rosalina; Edi Suharto (Akuisisi : Jurnal Akuntansi, 2025)
This study aims to analyze and create the program cash recording information system at PT Bara Prima Multi Teknovasi. Observations and interviews with the owner were used to collect data. The result from using a qualitative research approach shows the cash is still manually recorded in Microsoft Excel, and concsequently a long withdrawal data to process and limited information. Therefore, this study Design a web-based cash recording information system, making it easily to manage, update, and accessible anywhere.The waterfall model was applied in system development. Data Flow Diagram and Entity Relationship Diagram are the tools that the writers gonna use for the system design, and implement that using PHP with laravel as a framework. The result in this study show web-based cash recording information system can help the work of recording to be faster and more accurately.